Preoperative excessive lateral anterior tibial subluxation is related to posterior tibial tunnel insertion with worse sagittal alignment after anterior cruciate ligament reconstructions - Liu, An; Ye, Xiaojun; Li, Congsun; Yang, Weinan; Yan, Shigui; Xin, Zengfeng; Wu, Haobo (Frontiers in Surgery, 2022)
Objective: To investigate whether preoperative lateral anterior tibial subluxation (LATS) measured from magnetic resonance imaging (MRI) can influence tibial insertion and postoperative sagittal alignment after anterior cruciate ligament reconstructions (ACLRs). Methods: 84 patients who underwent single-bundle ACLRs were retrospectively investigated. Among them, 39 patients (LATS of < 6 mm) 23 patients (LATS of ≥ 6 mm and < 10 mm ) and 22 patients (excessive LATS of ≥ 10 mm) were defined as group 1, 2 and 3, respectively. LATS, the position of graft insertion into tibia as ratio of anterior-posterior width (AP ratio) and the sagittal graft angle (SGA) were postoperatively assessed from MRI at 2-year follow-up. Following linear regression analyses were employed. Results: The group 3 exhibited the largest preoperative LATS and remained the most postoperative LATS. Moreover, the group 3 possessed the most posteriorly located tunnel insertion with the largest AP ratio and the most vertical graft orientation. Of all included patients, a moderate correlation was demonstrated between pre- and postoperative LATS (r = 0.635). A low correlation was observed between preoperative LATS and AP ratio (r = 0.300) and a moderate correlation was displayed between AP ratio and SGA (r = 0.656). Conclusion: For ACL injuries with excessive LATS (≥ 10 mm), most posteriorly located tibial insertion was found out, and worse sagittal alignment containing high residual LATS was associated with more vertical graft orientation following ACLRs.